ANALYSIS OF THE INFLUENCE OF PROMOTIONS AND PRICES ON INTEREST IN PURCHASING SATYA SANTOSHA PRODUCTS IN DENPASAR CITY - Swara, Ega Paudra; Sumaji, Yoseva Maria Pujirahayu (PERFORMA, 2024)
This research was conducted to determine and analyze the influence of promotions and prices on purchasing interest. This research uses quantitative methods with the population used being people who consume chicken meat in Denpasar City aged 16 to 60 years. The number of samples used was 120 people. The sampling technique was carried out using the purposive sampling method. The results of the research that has been carried out find that the promotion variable has a significant ef ect on buying interest and the price variable has a significant ef ect on buying interest.